The Role of Lipid Metabolism in Gastric Cancer - Cui, Meng-Ying; Yi, Xing; Zhu, Dan-Xia; Wu, Jun (Frontiers in Oncology, 2022)
Gastric cancer is widespread in the world with extensive metastasis and high mortality. Chemotherapy is one of the main treatments for metastatic gastric cancer, but drug resistance limits the effectiveness of chemotherapy and leads to treatment failure. The mechanism of chemotherapy resistance in gastric cancer is complex and multifactorial, among which lipid metabolism plays an important role. Increased synthesis of new lipids or uptake of exogenous lipids contributes to the rapid growth of cancer cells and tumor formation. Lipids not only form the structural basis of biofilms, but also serve as signal molecules and energy sources. Interestingly, lipid metabolism can also induce drug resistance in gastric cancer cells by reshaping the tumor micro-environment. This article reviews the new mechanisms of lipid metabolism in gastric cancer and the metabolic pathways related to chemotherapy resistance. In particular, we also discussed the effects of lipid metabolism on autophagy, biomarkers treatment and drug resistance in gastric cancer from the perspective of lipid metabolism. In conclusion, elucidating the mechanism of lipid metabolism reprogramming and resensitization to chemotherapy in gastric cancer cells will provide new insights into the development of promising therapies and provide scientific treatment for the clinical use of lipid-key enzyme inhibitors as cancer chemical sensitizers.